2021
DOI: 10.3390/ph14121230
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-Related Genetics as Predictive Biomarker of Clinical Remission in Adalimumab-Treated Patients Affected by Crohn’s Disease: A Pilot Study

Abstract: Adalimumab (ADA) is a human anti-tumor necrosis factor (TNF-α) monoclonal antibody used in inflammatory bowel diseases, such as Crohn’s disease (CD). Vitamin-D (VD) is important for biological functions, such as the modulation of expression of genes encoding enzymes and transporters involved in drug metabolism and transport. ADA trough levels were associated with VD concentrations in patients with IBD, but no data are present in the literature concerning VD pathway-related gene single-nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“… 9 Vitamin D levels can also influence the initial response to anti-TNF-α medication in patients with IBD. 159 In addition, some vitamin D related genetic variants have already been reported associated with the remission after adalimumab treatment in CD patients, 172 which potentially supports that vitamin D might affect the efficacy of adalimumab. Moreover, as gut-tropic integrin α4β7 is another IBD immune treating target, vitamin D can downregulate gut-tropic integrin, α4β7, expression on immune cells, and higher 25(OH)D is associated with lower α4β7 positive PBMC levels and α4β7 positive intestinal leukocytes.…”
Section: Predictive Role For Vitamin D During Ibdmentioning
confidence: 92%
“… 9 Vitamin D levels can also influence the initial response to anti-TNF-α medication in patients with IBD. 159 In addition, some vitamin D related genetic variants have already been reported associated with the remission after adalimumab treatment in CD patients, 172 which potentially supports that vitamin D might affect the efficacy of adalimumab. Moreover, as gut-tropic integrin α4β7 is another IBD immune treating target, vitamin D can downregulate gut-tropic integrin, α4β7, expression on immune cells, and higher 25(OH)D is associated with lower α4β7 positive PBMC levels and α4β7 positive intestinal leukocytes.…”
Section: Predictive Role For Vitamin D During Ibdmentioning
confidence: 92%
“…It is now known that polymorphisms of the VDR gene can lead to functional changes modulating the regulatory effects of vitamin D, as well as in the immune response. Indeed, associations between clinical response or remission during anti-TNFα therapy and VDR polymorphisms has been reported [15,16], but to our knowledge, this is the first study that has investigated the possible involvement of rs11568820 SNP in TNF-i treatment response.…”
Section: Discussionmentioning
confidence: 94%
“…For this reason, VDR polymorphisms with functional roles could be associated with clinical outcome and achieving remission in patients undergoing TNF-i treatment. Cusato et al described an association between VDR rs1544410 SNP and clinical remission at three months of TNF-i therapy in patients with inflammatory bowel disease (IBD) [15]. A study in patients with axial spondyloarthritis showed different improvements in C-reactive protein (CRP) and disease activity scores after 3 and 6 months of TNF-i therapy, depending on the genotype of the VDR polymorphisms rs2228570, rs731236 and rs7975232 [16].…”
Section: Introductionmentioning
confidence: 99%